Niveles séricos de estrógeno (estradiol) y su relación con perfil lipídico en mujeres en etapa postmenopáusica que acuden al Centro de Salud N° 2 de la ciudad de Loja - Torres Sánchez, Nathaly Elizabeth (2018)
During postmenopause, women experience unfavorable changes in the lipid profile, have high levels of total cholesterol, have a low density lipoprotein (LDL) cholesterol and a decrease in high density lipoprotein (HDL) tends to decrease, Attributing these variations to the low serum concentrations of estrogen. The present study entitled "Serum levels of estrogen (estradiol) and its relationship with lipid profile in postmenopausal women attending the health center No. 2 of the city of Loja", aimed to establish the relationship between levels serum estrogen (estradiol) and lipid profile in women who are in postmenopausal stage, determine the levels of the profile by means of the spectrophotometry technique and the knowledge of the investigation. The study was of a quantitative, descriptive and cross-sectional type. It consisted of 75 women who were in the postmenopausal stage in which the estradiol concentration was determined, which was in 71% of the selected population within the normal range that is of 5-30 pg / ml, 24% with values higher than 30 pg / ml and 5% presented estradiol values lower than 5 pg / ml. The lipid concentration was quantified obtaining that only 53% of the population had normal cholesterol levels, 36% of triglycerides, 49% of LDL-C and 41% of HDL-C. Key words: postmenopausal women, estradiol, lipid profile.